Give my swiss chards to Broadway : the Broadway lover's cookbook - Glick, Gideon; Roberts, Adam D. (Countryman Press, 2022)
"An exhilarating, pun-filled love letter to musicals, with 50 Broadway-inspired recipes. Good food and trivia and authors who sing-these are a few of our favorite things! Tony-nominated actor Gideon Glick and food writer Adam Roberts have teamed up to write the ultimate cookbook for theater lovers. This collection of musical-inspired recipes includes dishes like Yolklahoma!, Clafoutis and the Beast, Yam Yankees, Dear Melon Hansen, and more. And while readers are sure to be charmed by the names, the recipes themselves will have them sticking around for the food, glorious food! Thoughtfully assembled by two veritable Broadway experts, this book is sure to result in some enchanted eating. Each dish comes with a brief history of the show that inspired it, a summary of the plot, and "Listening Notes" chock-full of behind-the-scenes trivia. Complete with lively illustrations from celebrated theatrical illustrator Justin "Squigs" Robertson, Give My Swiss Chards to Broadway makes every meal feel like a night at the theater"--